The production risk of broiler farm management at plasma breeders: Evidence from Indonesia - Suwarta Suwarta; Rita Hanafie (Publisher of Widyagama University of Malang (UWG Press), 2021)
The broiler chicken business is essential to providing national meat consumption in Indonesia. However, the business also faces a very significant management risk. The purpose of this research is to study broiler farm management and the effect of its business management on the production and production risk. This research was conducted in Lamongan regency of East Java by interviewing broiler chicken farmers and using descriptive and multiple linear regression analysis. The results of the research show that the implementation of broiler farm management reached 73.48% of ideal situation, with planning reaching 67.64% ideal situation, 65.58% for ideal organizing, 84.18% for optimal direction, 74.43% for ideal coordination, and 77.58% for ideal control. Also, the management had a positive influence on the production of the broiler livestock business, with an elasticity of 0.700. The management had a negative effect on the risk of production of broiler livestock business with the elasticity of 0.237. Production risk was negatively affected by the number of chicks and the amount of feed. To provide support for breeders in their business, it is necessary to have a policy of low cost of broiler cultivation, especially the cost of chicks and feed, by setting DOC prices and cheap or cheaper feed. Besides, it is required to develop cooperation with companies using broiler primary products, as well as certain policies so that there will be businesses that use broiler primary products as their main ingredient.JEL Classification D13; Q02; Q12